2022
DOI: 10.1002/ece3.9160
|View full text |Cite|
|
Sign up to set email alerts
|

Pattern of play behavior in infant (age 1 to 12 months) white‐headed langurs in limestone forests, southwest China

Abstract: Play behavior is a significant trait of immature nonhuman primates (hereafter primates) that plays an important role in sensory, locomotor, socio‐cognitive, and developmental processes. It has been suggested that the function of play is to practice and improve motor skills related to foraging, avoiding predators, attracting mates, raising offspring, and strengthening the skills needed for the formation and maintenance of social bonds. From September 2009 to August 2010, we investigated the play behavior of 1–1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 84 publications
0
1
0
Order By: Relevance
“…In the recent article by Yang et al ( 2022 ), the authors have confirmed that the Acknowledgment section should read as follows.…”
mentioning
confidence: 94%
“…In the recent article by Yang et al ( 2022 ), the authors have confirmed that the Acknowledgment section should read as follows.…”
mentioning
confidence: 94%